SUMMARY OF THE SPECIES POA BULBOSA L. (POACEAE) COMMON IN THE FERGANA VALLEY (World Bulletin of Social Sciences, 2021)
Poa L. (Poaceae Barnhart) is one of the largest categories of the family. This synopsis gives a broad concept of Poa bulbosa L. plants, its distribution and properties. This synopsis provides information about the types of a given species, morphology, synonyms, life form, phenology, ecology, general distribution and meaning, reliable information is given.